Description of Religious Coping in Drug Users - Rosmiati, Rosmiati; Firdaus, Aris; Suhanda, Suhanda (Asy-Syifa : Journal of Science and Technology Nursing, 2024)
Purpose:  to find out how the picture of coping religiosity in drug users in Class IIB Correctional Institution, Ciamis Regency. Methods: This study used quantitative methods with descriptive research design, the sampling technique in this study was total sampling. Results: the study showed that of the 31 respondents regarding coping religiosity in drug users in Class IIB Correctional Institution Ciamis Regency, it was concluded from the results of data processing that most of the religiosity was in the good category as many as (31) people, with a frequency of (100%). This is supported by routine recitation activities carried out 3 times a week. Conclusion: Coping Religiousity in Class IIB Correctional Institution Ciamis Regency is categorized as good. This is evidenced by the fulfillment of factors that indicate good religious coping, namely Prayer, Dhikr, Praying, Reading the Qur'an. All respondents have all four factors.